Complete Atrioventricular Block in Acute Rheumatic Fever with Clinical Presentation of Syncope and Abdominal Pain: A Case Report - Trisna Ardani, Nyoman Intan; Gede Aditya (Archives of The Medicine and Case Reports, 2024)
Acute rheumatic fever (ARF) is a systemic inflammatory disease following group A streptococcus infection that can affect various organs, including the heart. The most common cardiac manifestation is pancarditis, which can cause various arrhythmias. Complete atrioventricular (AV) block is a rare cardiac complication of ARF, especially in adult patients. We report the case of a 30 year old man who came to the emergency room with the main complaint of abdominal pain, nausea, vomiting, and a history of syncope. He also had a history of fever and joint pain. Physical examination and electrocardiogram (ECG) showed complete AV block. The patient was admitted to the ICU and given medical therapy for ARF and complete AV block. After several days of treatment, his complete AV block recovered to sinus rhythm, and his clinical symptoms improved. This case report highlights the importance of considering ARF as a differential diagnosis in young adult patients with complete AV block and systemic symptoms. Fast and appropriate treatment can improve the patient's prognosis.